Penguatan Pendidikan Berkelanjutan Melalui Sosialisasi Knowledge Management Di SMPS Kasih Ibu Patumbak - Julianto Hutasuhut; Adrial Falahi; Ardhansyah Putra; Abd.Rasyid Syamsuri; Fathin Abdullah (CITAKARYA, 2025)
Sustainable education is a collective responsibility, as the ever-evolving nature of the world demands continuous advancement in knowledge, skills, and technological competence. Embracing lifelong learning and engaging in educational collaboration not only reinforces sustainable education but also affirms that every individual has the right to grow, aspire, and contribute to meaningful global change. A nation’s development and well-being are deeply influenced by the quality of its educational system. High-quality education cultivates human resources who are capable, innovative, and highly competitive essential traits for driving progress across sectors. At the core of educational quality lies teacher performance, making educators pivotal agents in the advancement of learning outcomes. Implementing Knowledge Management (KM) stands out as a strategic approach to enhance this process. This community service initiative (PkM) sought to disseminate and promote Knowledge Management practices at Kasih Ibu Private Junior High School Patumbak through socialization, educational sessions, and structured mentoring involving the school’s teaching staff. The outcomes revealed improved teacher understanding of KM concepts, along with increased motivation to engage in knowledge sharing, utilization, and management to support their professional responsibilities.Challenges such as limited technological infrastructure and resistance to new concepts highlighted the need for collaborative teams and institutional backing. Nonetheless, the initiative positively influenced teacher performance and fostered a sustainable culture of knowledge exchange. Moving forward, reinforcing these efforts through sustainable education, provision of appropriate technological tools, and systematic evaluation is essential to ensure the long-term effectiveness of Knowledge Management practices.